The Concept of Nature-Based Children's Education (Study of the Interpretation of Verses and Hadiths Related to Fitrah) - Amir, Rezki Sulfitri; Hafidhuddin, Didin; Indra, Hasbi; Husaini, Adian (PT FORMOSA CENDEKIA GLOBAL, 2024)
The focus of the problem in this research is the preparation of the concept of nature-based children's education which was developed from analysis of interpretations of verses and hadiths related to nature. This analysis is strengthened by the opinions of tafsir scholars and tarbawi scholars regarding the meaning of fitrah so that it can be translated into an ideal child education concept. The data collection technique emphasizes aspects of text analysis and study. The methods used are the tafsir Madhuri and tafsir tahlili methods by collecting all the verses related to fitnah, and then analyzing and explaining the meanings contained in the verses.The research results show that the foundation of nature-based education is the Koran, hadith, ijma', and qiyas. The aim is to strengthen the foundation of faith in children, give birth to people with noble character, give birth to people who always preserve nature, and give birth to people whose obsession is the afterlife and whose goal is the approval of Allah. The solutions to these challenges are a sense of responsibility, sincerity for God alone, knowledge about children's readiness, fulfilling resources according to ability, and building good synergy between parents and educational institutions.